Guillain-Barré syndrome following acute head trauma. Issue 740 (June 1987) - Duncan, R.; Kennedy, P. G.
Abstract : A case of classical Guillain-Barré syndrome following acute head trauma is described. The association of Guillain-Barré syndrome with head injury per se is not well recognized, and a possible immunological explanation is proposed.